Distribution and Abundance of the Kittlitz's Murrelet Brachyramphus brevirostris in Selected Areas of Southeastern Alaska - Kissling, Michelle L.; Lukacs, Paul M; Lewis, Stephen B.; Gende, Scott M.; Kuletz, Katherine J.; Hatch, Nicholas R.; Schoen, Sarah K.; Oehlers, Susan (ScholarWorks at University of Montana, 2011)
We conducted boat-based surveys for the Kittlitz’s Murrelet Brachyramphus brevirostris during the breeding season in southeastern Alaska from 2002 to 2009. We completed a single survey in seven areas and multiple annual surveys in three areas. Although surveys spanned a broad geographic area, from LeConte Bay in the south to the Lost Coast in the north (~655 km linear distance), roughly 79% of the regional population of Kittlitz’s Murrelet was found in and between Icy and Yakutat bays (~95 km linear distance). The congeneric Marbled Murrelet B. marmoratus outnumbered the Kittlitz’s Murrelet in all areas surveyed except Icy Bay; in fact, Kittlitz’s Murrelet abundance constituted a relatively small proportion (7%) of the total Brachyramphus murrelet abundance in our survey areas. In areas for which there are multiple years of survey data, Kittlitz’s Murrelet abundance varied considerably, whereas Marbled Murrelet abundance was comparatively stable during the same time period. Since the southern distribution of this species has likely narrowed over the last 50 years, and the distribution of the Kittlitz’s Murrelet appears to be restricted to glacially influenced marine waters in southeastern Alaska, we expect that any future changes in glacial extent will likely affect this species and its long-term persistence in the region.